N-Butanol production from lignocellulosic biomass hydrolysates without detoxification by Clostridium tyrobutyricum Δack-adhE2 in a fibrous-bed bioreactor. (October 2019) - Li, Jing; Du, Yinming; Bao, Teng; Dong, Jie; Lin, Meng; Shim, Hojae; Yang, Shang-Tian
Graphical abstract: Highlights: n -Butanol production from lignocellulosic biomass hydrolysates was studied. Engineered Clostridium tyrobutyricum was immobilized in a fibrous-bed bioreactor. Co-utilization of glucose and xylose in the hydrolysates was achieved. High-level butanol production was obtained from hydrolysates without detoxification. Techno-economic analysis shows the potential for industrial application. Abstract: Acetone-butanol-ethanol fermentation suffers from high substrate cost and low butanol titer and yield. In this study, engineered Clostridium tyrobutyricum CtΔ ack - adhE2 immobilized in a fibrous-bed bioreactor was used for butanol production from glucose and xylose present in the hydrolysates of low-cost lignocellulosic biomass including corn fiber, cotton stalk, soybean hull, and sugarcane bagasse. The biomass hydrolysates obtained after acid pretreatment and enzymatic hydrolysis were supplemented with corn steep liquor and used in repeated-batch fermentations. Butanol production with high titer (∼15 g/L), yield (∼0.3 g/g), and productivity (∼0.3 g/L∙h) was obtained from cotton stalk, soybean hull, and sugarcane bagasse hydrolysates, while corn fiber hydrolysate with higher inhibitor contents gave somewhat inferior results. The fermentation process was stable for long-term operation without any noticeable degeneration, demonstrating its potential for industrial application. A techno-economic analysis showed that n -butanol could be produced from lignocellulosic biomass using this novel fermentation process at ∼2.5/gal for biofuel application.